Enhancing adaptation tracking through NAPs and NDCs - Njuguna, Lucy; Nowak, Andreea C.; Giombini, Valentina; Muller, Lolita; Rosenstock, Todd (2024)
Following the adoption of the UAE Framework for Global Climate Resilience at COP 28 in Dubai, the Least Developed Countries Expert Group (LEG) was tasked with updating the guidelines for developing National Adaptation Plans (NAPs) to align with the new framework. This presentation, delivered at the 46th session of LEG, shares findings from an analysis of NAPs and Nationally Determined Contributions (NDCs) from African LDCs. It highlights opportunities to strengthen systems for monitoring and evaluating adaptation progress, helping countries track their efforts more effectively.